2015
DOI: 10.1002/jlcr.3256
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-14 radiolabeling andin vivobiodistribution of a potential anti-TB compound

Abstract: A potential anti-TB compound bearing a nitroimidazole moiety from iThemba Pharmaceuticals TB chemical library exhibits promising in vitro activity in the microplate almar blue assay (MABA) with a minimum inhibitory concentration (MIC) value of 3 µg/mL. It is equipotent to the front-line drug Isoniazid, but the compound is less toxic with an IC50 of >100 µg/mL. Therefore, this potential iThemba nitroimidazole, 4-([1,1'-[(14)C6]biphenyl]-4-ylmethyl)-9-nitro-3,4,5,6-tetrahydro-2H-imidazo[2,1-b][1,3,6]oxadiazocine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…This is gratifying as it indicates that the method followed is reliable although it indicates that the compound has no preference for TB in vivo . One would have expected higher lung uptake in the TB‐infected animals if the compound would have stayed intact in vivo . This is unexpected as the in vitro data suggest a higher MIC 99 value for this compound.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is gratifying as it indicates that the method followed is reliable although it indicates that the compound has no preference for TB in vivo . One would have expected higher lung uptake in the TB‐infected animals if the compound would have stayed intact in vivo . This is unexpected as the in vitro data suggest a higher MIC 99 value for this compound.…”
Section: Resultsmentioning
confidence: 96%
“…One would have expected higher lung uptake in the TB-infected animals if the compound would have stayed intact in vivo. 23 This is unexpected as the in vitro data suggest a higher MIC 99 value for this compound. The difference in vivo can possibly be explained by (1) that the compound is digested (broken down) in vivo and therefore only a part of the molecule (which no longer has anti-TB properties) is followed via the C-14 tracer or (2) the compound has no binding affinity for TB cells even if it has a high toxicity towards the cells.…”
Section: Tissue Distribution Studymentioning
confidence: 96%
“…The unsaturated benzoxadiazocine 8 was prepared as a novel heterocycle [8], and reaction of two equivalents of 2H-azirines with chlorosulfonyl isocyanate gives the oxadiazocinones 9 [9]. Various ring-fused derivatives are also known including the purine-fused compounds 10 [10], and the imidazo[2,1-b] fused compounds 11 which are active against tuberculosis and a range of other tropical diseases [11,12]. Compound 12 is formed as a byproduct in a Pictet Spengler reaction [13].…”
Section: Resultsmentioning
confidence: 99%
“…It has already been shown that concentration of a particular drug in the lung for example may be higher than that in the plasma (Sonopo et al, 2015). Indeed, this trend is shown to obtain for the first-line TB drugs PZA, RIF, and INH whose concentrations in the lungs of uninfected primate species (baboons) were higher than in the plasma (Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 90%